Next generation tutor-matching and education platform - Chang, Callista Rossary (Nanyang Technological University, 2022)
Within the rapidly growing supplementary education industry in Singapore lies significant inefficiencies and practices that do not meet the needs of the modern world. Learnable was proposed as a next generation tutor-matching and education platform with a large emphasis providing parents and tutors the necessary tools to improve learning outcomes for children in Singapore.